GNAS, GNAQ, and GNA11 alterations in patients with diverse cancers. Issue 20 (11th September 2018) - Parish, Austin J.; Nguyen, Vi; Goodman, Aaron M.; Murugesan, Karthikeyan; Frampton, Garrett M.; Kurzrock, Razelle
Abstract : Background: Advances in deep sequencing technology have uncovered a widespread, protumorigenic role of guanine nucleotide‐binding (G protein) α (GNA) subunits, particularly GNA subunits Gs ( GNAS ), Gq ( GNAQ ), and G11 ( GNA11 ) ( GNA* ), in a diverse collection of malignancies. The objectives of the current study were: 1) to determine GNA* aberration status in a cohort of 1348 patients with cancer and 2) to examine tumor mutational burden, overall survival rates, and treatment outcomes in patients with GNA *‐positive tumors versus those with tumors that had wild‐type GNA* . Methods: For each patient, clinical and genomic data were collected from medical records. Next‐generation sequencing was performed for each patient (range, 182‐236 genes). Results: Aberrations of GNA* genes were identified in a subset of patients who had 8 of the 12 cancer types examined, and a significant association was observed for appendiceal cancer and ocular melanoma ( P < .0001 for both; multivariate analysis). Overall, 4.1% of the cancer population was affected. GNA* abnormalities were associated with higher numbers of co‐alterations in univariate (but not multivariate) analysis and were most commonly accompanied by Aurora kinase A ( AURKA ), Cbl proto‐oncogene ( CBL ), and LYN proto‐oncogene ( LYN ) co‐alterations (all P < .0001; multivariate analysis). GNA* alterations were correlated with a trend toward lower median overall survival ( P = .085). The median tumor mutational burden was 4 mutations per megabase in both GNA* ‐altered and GNA* wild‐type tumors. For this limited sample of GNA* ‐positive patients, longer survival was not correlated with any specific treatment regimens. Conclusions: In the current sample, the genes GNAS, GNAQ, and GNA11 were widely altered across cancer types, and these alterations often were accompanied by specific genomic abnormalities in AURKA, CBL, and LYN . Therefore, targeting GNA* alterations may require drugs that address the GNA* signal and important co‐alterations. Cancer 2018;00:000‐000. © 2018 American Cancer Society. Abstract : The guanine nucleotide‐binding protein (G protein) subunit α (GNA*) genes GNAS, GNAQ, and GNA11 are altered ubiquitously across many diverse cancer types. Future development of novel therapies targeting these GNA* aberrations and important co‐alterations is needed.